INFLAMMATORY BOWEL DISEASE, SOCIAL IMPACTS AND QUALITY OF LIFE: A LITERATURE REVIEW: DOENÇA INFLAMATÓRIA INTESTINAL, IMPACTOS SOCIAIS E QUALIDADE DE VIDA: UMA REVISÃO DA LITERATURA - Lima Ferreira, Ialy Beatriz; de Souza, Maria Clara Teles; de Lima, Raísa Kettlyn Simões (Revista de Ciências da Saúde Nova Esperança, 2021)
Inflammatory bowel disease (IBD) is a continuous total or partial inflammation of the digestive tract, with Crohn’s disease and ulcerative colitis being the most common forms of presentation. The most frequent signs and symptoms consist of abdominal pain, fatigue, bloody stools, diarrhea, weight loss, and vomiting, and there may be extra-intestinal manifestations. In developed countries, an increased incidence of IBD has been observed, particularly in young people of working age, impacting their quality of life as well as physical, social and psychological aspects. This is because once diagnosed with IBD, individuals encounter coping challenges, difficulties in acceptance, and lifestyle changes. Therefore, we sought to analyze the social impacts and quality of life of patients diagnosed with Inflammatory Bowel Disease. A literature review was conducted in PubMed, SciELO, BVS and LILACS databases, 20 articles met the established criteria, of which 10 were selected to compose the study. Articles published between 2016 and 2021 and relevant to the topic were included, and those that did not meet the inclusion criteria or did not comprise primary data, and were duplicates were excluded. The analyzed studies showed that there was a reduction in quality of life in patients with IBD, presenting as main factors associated with this restriction the disease activity, socioeconomic factors, and the patient’s age. It was denoted that this negative aspect causes limitations, mainly in the biopsychosocial performance of patients with this condition. Therefore, it is noteworthy that biopsychosocial impacts result from the manifestation of Inflammatory Bowel Disease, which demonstrates the need for a qualified and humanized multidisciplinary follow-up during the evolution of these patients.